Some Engineering Properties of Garlic (Alliumsativum L) - Manjunatha, M; Samuel, D.V.K; Jha, S K (Journal of Agricultural Engineering, 2008)
Garlic (Allium sativum L.) (Cultivar G-282) grown in Indian subcontinent was selected to establish some of its useful engineering properties. The shape, average diameter, weight, bulk density, segment number of whole garlic, average length, width, thickness, geometric mean diameter, sphericity and mass weight of 1000 garlic segment were determined (at 40.50 % moisture content on wet basis) as round, 5.12 cm, 28.64 g, 414.40 kg/mÂ³, 16.32, 26.25 mm, 10.36 mm, 8.73 mm, 13.34 mm, 0.51 and 1813.60 g, respectively. In the moisture content range from 23.05 to 40.50 %(w.b.), the terminal velocity, angle of repose, specific gravity, compressive and shear forces of garlic segment increased from 7.18 to 12.24 m/s, 25.53 to 37.50 degree, 0.90 to 0.97, 2.25 to 10.70 kg and 1.75 to 2.83 kg, respectively, while bulk density decreased from 483.10 to 449.76 kg/mÂ³. The static coefficient of friction increased on three surfaces, namely, teak wood (0.46 to 0.53), aluminum (0.38 to 0.48) and mild steel (0.34 to 0.41) with increase in moisture content from 23.05 to 40.50 % (w.b.).